Impact of MHD radiative flow of hybrid nanofluid over a rotating disk. (August 2021) - Waqas, Hassan; Farooq, Umar; Naseem, Rabia; Hussain, Sajjad; Alghamdi, Metib
Abstract: Purpose: In this article, we scrutinized the impacts of non-linear thermal radiations on S W C N T − T i O 2 & M W C N T − C o F e 2 O 4 nanoparticles suspended in water-based hybrid type nanofluid flow over rotating disk. The effects of nonlinear thermal radiation are considered. The flow is induced through rotating disk. There is a huge market for nanotechnology, and the development of these materials can be predicted to be very light. The effects of shape factors are also considered. Nanomaterials are characterized into different types due to its shapes, features and size of materials. General types nanomaterials catagories include carbon nanotubes. Further CNTs are divided into two different shapes includes single wall carbon nanotudes (SWCNTs) and multi-wall carbon nanotubes (MWCNTs). Carbon nanotubes have significants applications in energy storages, damping and fracture toughness stiffness. Carbon nanotubes are most commonly used in the fields of energy conservation, thermal stability, nanotubes transistors and electromagnetic fields and many areas. Methodology: The system of governing partial differential equations are reduced to dimensionless ordinary equations by using similarity transformations and then solved with bvp4c in-built function Matlab. behavioral analysis of velocity components and heat transfer of different parameter values are evaluated utilizing graphs. Findings: The results shows that Velocity components are reduces via larger estimation of magnetic parameter. The solid particle frictions improves the velocity field. temperature ratio parameter aid to improves the heat transfer. Furthermore temperature is reduced via Prandtl number.